PENGARUH JENIS FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH BESAR (Capsicum annum L.) - Hadianur Hadianur; Syarifuddin Syarifuddin; Elly Kesumawati (Jurnal Agrotek Lestari, 2018)
This study aims to determine the effect of mycorrhizal fungi types on the growth and  yield of red pepper plants (Capsicum annum L.). This research used non factorial Completely Randomized Design (RAL) with 3 replications. The factor studied is the factor of mycorrhizal, which consists of 4 levels, namely: Without Mycorrhizal, Mycorrhiza Glomus sp., MikorizaGigaspora sp., Mixture Mikoriza Glomus sp. and Gigaspora sp. The parameters studied were nutrient uptake of N and P, fresh and dry weight of vegetative and generative phases, root biomass (fresh and dry) vegetative and generative phases, yield potentials per plant, vegetative and generative root phase roots, and mycorrhiza infection rates (%). The results of this study indicate that the type of mycorrhizal fungi. The type of mycorrhizal fungi has a very significant effect on the fresh and dry weighted weights, the fresh and dry root weight and the vegetative root phase length, and have no significant effect on N and P nutrient uptake, fresh and dry root weight, root length, yield potential/plant and mycorrhizal infection. The best type of mycorrhizal fungi for growth and yield of red pepper plants is Gigaspora sp.Keywords: Biomass, Glomus sp., Gigaspora sp.